Spined Soldier Bug, Podisus maculiventris (Say) (Insecta: Hemiptera: Pentatomidae) - David B. Richman; Frank W. Mead; Thomas R. Fasulo (EDIS)
Revised! EEN-Y231, a 5-page illustrated fact sheet by David B. Richman, Frank W. Mead, and Thomas R. Fasulo, is part of the Featured Creatures collection. It describes this medium-sized, spiny-shouldered, predatory stink bug which preys on a wide variety of other arthropods, including several important economic pests — distribution, description, life cycle, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, August 2010.